2016
DOI: 10.1080/17550874.2017.1283649
|View full text |Cite
|
Sign up to set email alerts
|

Testing the importance of a common ectomycorrhizal network for dipterocarp seedling growth and survival in tropical forests of Borneo

Abstract: Background: Connections between mature trees and seedlings via ectomycorrhizal (EcM) hyphal networks existing in dipterocarp-dominated tropical rain forests of South-east Asia could have strong implications for seedling growth and survival and the maintenance of high diversity in such forests. Aim: To test whether EcM hyphal network connections are important for the growth and survival of dipterocarp seedlings. Methods: We conducted four independent experiments that prevented contact of experimental seedlings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Tansley review New Phytologist tropical ECM trees found evidence that seedlings with access to EMNs perform better than those outside EMNs (Onguene & Kuyper, 2002;McGuire, 2007). Recent studies have found no evidence of active EMNs in forests dominated by ECM O. mexicana in Panama (Corrales et al, 2016b) or multiple dipterocarp species in Borneo (Brearley et al, 2016). Norghauer & Newbery (2016) provided evidence that a putative ECM fungal network may negatively affect the long-term survival of seedlings and saplings of Microberlinia bisulcata (Fabaceae) in Cameroon through deleterious juvenile-to-adult nutrient drains over multiple masting events.…”
Section: Reviewmentioning
confidence: 99%
“…Tansley review New Phytologist tropical ECM trees found evidence that seedlings with access to EMNs perform better than those outside EMNs (Onguene & Kuyper, 2002;McGuire, 2007). Recent studies have found no evidence of active EMNs in forests dominated by ECM O. mexicana in Panama (Corrales et al, 2016b) or multiple dipterocarp species in Borneo (Brearley et al, 2016). Norghauer & Newbery (2016) provided evidence that a putative ECM fungal network may negatively affect the long-term survival of seedlings and saplings of Microberlinia bisulcata (Fabaceae) in Cameroon through deleterious juvenile-to-adult nutrient drains over multiple masting events.…”
Section: Reviewmentioning
confidence: 99%
“…McGuire (2007) used a graded set of meshes to exclude hyphae and roots reaching Dicymbe corymbosa seedlings around adult trees of this species in a forest in Guiana, and found decreased growth and survival when ECM hyphae were excluded. Brearley et al (2016) in a more extensive set of four experiments using mesh treatments too, in Bornean forest (Sabah), could find little evidence for ECM networks assisting seedling growth and survival of five dipterocarp species. In these three examples, the test (seedling) species were all shade-tolerant.…”
Section: Introductionmentioning
confidence: 94%
“…Brearley et al. () in a more extensive set of four experiments using mesh treatments too, in Bornean forest (Sabah), could find little evidence for ECM networks assisting seedling growth and survival of five dipterocarp species. In these three examples, the test (seedling) species were all shade‐tolerant.…”
Section: Introductionmentioning
confidence: 98%
“…Dipterocarps have long been known to be ectomycorrhizal (Singh 1966) with ectomycorrhizas often credited as promoting faster growth rates and the high species diversity and dominance of the family. Brearley et al (2016) combined four independent studies that manipulated connection to an ectomycorrhizal hyphal network and found very little supporting evidence that this network influenced seedling growth or survival over the short term. They hypothesised this was due to low host specificity of ectomycorrhizal fungi meaning that there would be little chance for adult trees to exclusively support kin through a hyphal network and it would not, therefore, provide an adaptive benefit.…”
Section: Mycorrhizas and Soil Processesmentioning
confidence: 99%
“…The Asian dipterocarps are found in India (Antin et al 2016), Bangladesh, Nepal, Sri Lanka and the Andaman Islands, in the seasonal forests of Thailand (Disyatat et al 2016), Cambodia (Kenzo et al 2016b), Vietnam (Dong et al 2016 Dipterocarps are found across Malesia, throughout the Malay peninsula (Chong et al 2016;Kenzo et al 2016a;Ng et al 2016;Yamada et al 2016), Sumatra, Java, and in Borneo (Ang et al 2016;Brearley et al 2016;Dent and Burslem 2016;Nutt et al 2016;Saner et al 2016) they reach their highest species diversity ( Figure 2). East of Wallace's line, in neighbouring Sulawesi, diversity decreases markedly and although dipterocarp ranges extend to New Guinea (Figure 2), dipterocarp species constitute a much smaller component of the forest canopy.…”
mentioning
confidence: 99%